Relationship selling impact on sales effectiveness: an evaluation from a health insurance agent’s perspective - Santosh Nayak; Satish Kumar; Rita Rani Chopra; Ankitha Shetty (Insurance Markets and Companies)
This research paper examines the relationship selling impact on sales effectiveness in Health Insurance from an agent’s perspective. The study analyzed primary data by personal interaction with respondents in the Karnataka region, India, and used descriptive research with stratified sampling. A sample size of 407 health insurance agents was selected for this study from the age group between 18 to 60 years from diverse backgrounds. The research methodology involves constructing a regression model using the SPSS tool to analyze the data. The findings show that personal interaction determinants have positive and statistically significant effects on sales effectiveness, however, customer dependency and self-discipline have negative and statistically significant impacts on sales effectiveness. The results support the models’ reliability and a good measure of construct validity. Variables like Interaction Intensity (II) and Customer Dependence (CD) (0.632), Personal Interaction (PI) and Customer Dependence (CD) (0.464), and Customer Oriented Selling (COS) and Cooperative Intentions (CI) (0.523) have relatively strong positive correlations, suggesting these pairs move together in the same direction. This implies that an agent’s personal resources can affect their ability to convert relationship-selling behavior to tangible sales results that can guide sales force recruitment and training. Similarly, the organizing and structuring of the sales force can be informed by the findings that customer relationship characteristics influence salespeople’s ability to translate relationship selling behavior into sales effectiveness.